Teacher Perceptions, Responses, and Attitudes towards Learning Supervision - Cahya Fajar Budi Hartanto; A.M. Wibowo; Mohamad Miftah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Learning supervision is one of the efforts to increase the teacher's role in carrying out their duties so that it is hoped that it can help develop teacher competence. However, supervision is often seen as a heavy burden that must be faced by teachers. This research was conducted to assess the perceptions, responses, and attitudes of teachers towards learning supervision. All three must be kept positive so that they become motivation and momentum to absorb input from supervisors. The results of the study show that teachers' perceptions of supervision in various regions in Indonesia are very different, some are already good and some are still lacking. The response of the teachers was generally good and made supervision a means of balancing, bridge and communication. Meanwhile, the attitudes of teachers tend to be low because they do not yet feel a good partnership between teachers and supervisors.